Recent progress in continuously tunable low-noise all-solid-state single-frequency continuous-wave laser based on intracavity locked etalon - Jin, Pixian; Wei , Jiao; Su , Jing; Lu, Huadong; Peng , Kunchi (Frontiers in Physics, 2022)
All-solid-state single-frequency continuous-wave (CW) lasers have been applied in many fields of scientific research owing to their intrinsic advantages of high beam quality, low noise, narrow linewidth, and high coherence. In atom-based applications, single-frequency lasers should also be continuously tuned to precisely match their wavelengths with the transition lines of the corresponding atoms. Continuous frequency tuning of the laser is mainly achieved by continuously scanning the laser cavity length after the intracavity tuning element etalon is locked to an oscillating laser mode. However, the modulation signals necessary in current etalon locking systems increase the noise of the continuously tunable lasers and in some respects limit their applications in Frontier scientific research. Moreover, the obtained continuous frequency tuning range with the etalon locking technique is restricted by the free spectrum range of the adopted etalon. In this paper, we systematically summarize recent progress of the continuously tunable single-frequency CW lasers based on intracavity locked etalon, including the advanced etalon locking techniques and the tuning range expansion approach. As a result, the low noise and high stable all-solid-state single-frequency CW tunable lasers are successfully developed.